Cytokinin/auxin balance in crown gall tumors is regulated by specific loci in the T-DNA - Akiyoshi, D. E. (1983)
Insertion of the transposon Tn5 into the T-region of the octopine Ti plasmid of Agrobacterium tumefaciens gives rise to crown gall tumors having altered morphology. Three loci within the T-DNA that control tumor morphology have been detected [Garfinkel, D. J., Simpson, R. B., Ream, L. W., White, F. F., Gordon, M. P. & Nester, E. W. (1981) Cell 27, 143-153]. They influence tumor size (tml), production of roots (tmr), or production of shoots (tms). Cytokinin and auxin levels in such mutant tumors were examined by HPLC/radioimmunoassay and HPLC/fluorescence assay, respectively. Free indoleacetic acid levels (in pmol/g) were: uninfected tobacco stem tissues, 128; wild-type A348 tumors, 295; tml mutant tumors, 307; tmr mutant tumors, 129; and tms mutant tumors, 70. Average trans-ribosylzeatin levels were correspondingly: 0.97, 48, 40, 0.54, and 1,400 pmol/g. trans-Ribosylzeatin/indoleacetic acid ratios were as high as 24 in shoot-producing tumors and as low as 0.003 in root-producing tumors. The evidence strongly suggests that tumor phytohormone levels are determined by genes in the T-DNA.